The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1088/2053-1591/ab73fa
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and photocatalytic performance of iron molybdate (Fe2(MoO4)3) for the degradation of endosulfan pesticide

Abstract: Iron molybdate was prepared via simple solution chemistry method and the photocatalytic degradation of a pesticide (endosulfan) was investigated under visible light irradiation. As-prepared (Fe 2 (MoO 4 ) 3 ) was characterized using scanning electron microscope (SEM), x-ray diffraction (XRD), energy dispersive x-ray spectra (EDX), diffused reflectance spectroscopy (DRS) and Zeta particle sizer techniques. The iron molybdate crystallite size was 36 nm, while grain size was in the range of 160-340 nm. The partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Upon going through deeply, it was observed that the technique or nanomaterials used for degradation have many issues, such as utilization of UV‐ light source, the origin of secondary pollutants, and time‐consuming. Parveen et al 67 have reported adsorption of ES on Fe 2 (MoO 4 ) 3 nanoparticles. The mineralization of many pollutants under similar conditions was also reported 68 .…”
Section: Comparative Study With Another Catalystsmentioning
confidence: 99%
“…Upon going through deeply, it was observed that the technique or nanomaterials used for degradation have many issues, such as utilization of UV‐ light source, the origin of secondary pollutants, and time‐consuming. Parveen et al 67 have reported adsorption of ES on Fe 2 (MoO 4 ) 3 nanoparticles. The mineralization of many pollutants under similar conditions was also reported 68 .…”
Section: Comparative Study With Another Catalystsmentioning
confidence: 99%
“…EDX spectroscopy results in Fig.4 bshow that a peak around 5.5 keV indicates Ag and O are dominant elements in the sample. The strong signal energy peak for Ag atoms around 5.5 keV is typical for absorbing metallic and Ag nanocrystals onto EC[9]. A single solid energy peak indicated the purity of Ag in the sample, whereas other study reports stated the presence of C (2.20 %) and O (22.04 %)[10] with synthesised AgNPs.…”
mentioning
confidence: 93%
“…The presence of POPs in textile effluents leads to a series of negative effects on the ecology [20][21][22]. Insecticides are used in households, agriculture, medical industry, etc., which enter into water sources, causing toxicity in the aquatic and terrestrial organisms, leading to alteration of the ecosystem, in addition to human health [23,24]. Photocatalytic degradation of organic pollutants by metal oxides has gained attention among researchers due to its efficacy in attacking contaminants of the environment [20,25,26].…”
Section: Introductionmentioning
confidence: 99%